Anticipating and addressing event-specific alcohol consumption among adolescents. - Pettigrew, Simone; Biagioni, N.; Jongenelis, M. (BioMed Central Ltd, 2016)
Background: Various specific events and celebrations are associated with excessive alcohol consumption and related harms. End-of-school celebrations such as Schoolies in Australia are of particular concern given high levels of documented harm among underage and young drinkers. The present study investigated high school students’ expectations of their Schoolies celebrations to inform future interventions to reduce adverse outcomes among members of this vulnerable group and other young people involved in similar rites of passage. Methods: A link to an online survey was distributed via high schools and Schoolies-related websites. The survey included qualitative questions that invited respondents to discuss (i) aspects of Schoolies they were looking forward to most and least and (ii) their perceptions of the likely consequences if they refrained from consuming alcohol during the event. In total, 435 students provided responses. Results: Respondents discussed the role of Schoolies in marking their transition to adulthood. Their comments revealed a cross-temporal focus indicating that Schoolies is simultaneously symbolic of the past, present, and future. Through its ability to enhance social interaction, alcohol was perceived to have a vital role in realising the potential of this event to signify and facilitate this temporal progression. Conclusions: Results suggest interventions that treat Schoolies as an isolated event that occurs in specific locations may fail to appreciate the extent to which these events transcend time for those involved. Instead, harm reduction is likely to involve a reconceptualisation of the event among both participants and authority figures to facilitate the provision of alternative pastimes to drinking during Schoolies that yield similar social benefits.